PENERAPAN ACTIVITY BASED MANAGEMENT (ABM) UNTUK MENINGKATKAN EFISIENSI BIAYA PADA TWO-M DIGITAL PRINTING - Putri, Viola Berliana; Bakhrudin, Bakhrudin; Berlianingtyas, Putri Ayu (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2025)
The purpose of this study is to determine the calculation of production Costing (ABC) method, and the Activity-Based Management (ABM) method. This study is applied research using a quantitative descriptive approach. The data sources used in this research consist of primary data, obtained through interviews, and secondary data, obtained through documentation. The results of the study indicate that the ABM method can identify and analyze value-added and non- value-added activities in the production process. In this study, Two-M Digital Printing calculated production costs using the ABM method amounting to IDR 960,902,707, while the ABC method resulted in a total of IDR 967,807,208, resulting in a cost difference of IDR 6,904,502. This difference indicates efficiency in the allocation of production costs. The difference arises due to the distinctions between the ABM and ABC methods in cost allocation, as the ABM method allows for the identification of non-value-added activities that lead to waste, thereby resulting in lower costs compared to the ABC method. The positive impact of this difference includes reduced cost waste, improved decision-making accuracy, and more effective resource allocation. The implementation of the ABM method provides a detailed understanding of production costs, helps identify value- added activities and waste, and enables more accurate improvements. Therefore, the ABM method can assist company management in making decisions to enhance operational efficiency and is useful for managing and controlling costs at Two-M Digital Printing.